2008
DOI: 10.1111/j.1365-2141.2008.07079.x
|View full text |Cite
|
Sign up to set email alerts
|

The evolving use of serum free light chain assays in haematology

Abstract: SummaryOver the last few years new immunoassays have emerged that allow the measurement of free immunoglobulin light chains (FLCs) in serum to a level of 2–4 mg/l and provide a much greater sensitivity than older methods, such as immunofixation, which is able to detect FLCs at a minimum concentration of 100–150 mg/l. The new FLC assay has enabled the detection of monoclonal protein in some patients with non‐secretory myeloma and amyloidosis that were previously undetectable. FLC measurements are quantitative, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
60
1
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(66 citation statements)
references
References 71 publications
(69 reference statements)
2
60
1
3
Order By: Relevance
“…The prognostic role of unbalanced light chain production has been described at urinary level (7) and, more recently, serum level (10,20). Our data confirm that a finding of excess light chains is a risk factor.…”
Section: Discussionsupporting
confidence: 85%
“…The prognostic role of unbalanced light chain production has been described at urinary level (7) and, more recently, serum level (10,20). Our data confirm that a finding of excess light chains is a risk factor.…”
Section: Discussionsupporting
confidence: 85%
“…In two patients, the serum FLC ratio was within the reference interval, although serum PE showed the presence of M-protein. It has been reported that in 10% of IIMM, the k/l ratio can be normal (11,12). However, in our study, serum PE was not helpful in diagnosing MM in eight patients (10%), and the M-protein was detected either by IFE or urine PE.…”
Section: Discussioncontrasting
confidence: 41%
“…1 Serum assays offer many advantages over the traditional, electrophoretic, urine FLC assays [2][3][4] and have been used widely as an aid for the diagnosis and management of myeloma patients. The International Myeloma Working Group (IMWG) guidelines currently recommend the use of serum FLC (sFLC) assays in diagnostic screening panels and as a "biomarker of malignancy" (involved-to-uninvolved sFLC ratio $100) defining the presence of multiple myeloma (MM) in the absence of other indications.…”
Section: Introductionmentioning
confidence: 99%